The return of epic formulas in various Italian translations of Kosovka djevojka (The Kosovo maiden) - Bradaš Marija (Balcanica, 2013)
This paper makes a comparative analysis of the various Italian translations of the famous Serbian popular poem Kosovka djevojka [The Kosovo Maiden] and illustrates the different interpretations and consequent translations of epic formulas in nineteenth- and twentieth-century Italy. The Parry-Lord oral formulaic theory, together with other important contributions in the field of oral studies, is a starting point for this analysis, which also takes into consideration the socio-cultural context in which these translations were produced. Translation solutions are therefore brought into relation with the poetics of individual translators and especially with the socio-cultural context of their time. Particular attention is devoted to the centuriesold Italian rhetorical tradition, which influenced even the greatest experts in popular poetry in their interpretation of the figures and clichés typical of oral production.